2014
DOI: 10.1038/jid.2014.137
|View full text |Cite
|
Sign up to set email alerts
|

Acute Wounding Alters the Beta2-Adrenergic Signaling and Catecholamine Synthetic Pathways in Keratinocytes

Abstract: Keratinocyte migration is critical for wound re-epithelialization. Previous studies showed that epinephrine activates the beta2-adrenergic receptor (B2AR), impairing keratinocyte migration. Here, we investigated the keratinocyte catecholamine synthetic pathway in response to acute trauma. Cultured keratinocytes were scratch wounded and expression levels of the B2AR and catecholamine synthetic enzymes tyrosine hydroxylase and phenylethanolamine-N-methyltransferase were assayed. The binding affinity of the B2AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 61 publications
1
31
0
1
Order By: Relevance
“…Th and Ddc in the catecholamine pathway were strongly expressed at E10.5. Catecholamines (CA) are synthesized by keratinocytes in response to wounding and CA signaling modulates wound healing (Schallreuter et al, 1995; Sivamani et al, 2014), but neither has previously been implicated in epidermal development. Two components of the Hippo signaling pathway, Amot and Vgll2, were also included in this early program.…”
Section: Resultsmentioning
confidence: 99%
“…Th and Ddc in the catecholamine pathway were strongly expressed at E10.5. Catecholamines (CA) are synthesized by keratinocytes in response to wounding and CA signaling modulates wound healing (Schallreuter et al, 1995; Sivamani et al, 2014), but neither has previously been implicated in epidermal development. Two components of the Hippo signaling pathway, Amot and Vgll2, were also included in this early program.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that factors within the chronic wound site, including Staphylococcus aureus and woundgenerated EPI (Sivamani et al, 2014) might induce the AMSC to release inflammatory cytokines and prolong the inflammatory phase, as previously reported in BM-MSC (Dasu et al, 2014). Therefore, we tested whether the beta-adrenergic receptor antagonist, timolol, could reverse the pro-inflammatory phenotype of AMSC that are subjected to these stimuli.…”
Section: Laboratory Studiesmentioning
confidence: 89%
“…In addition, AMSC have shown neovascularization and antioxidant potential, which are both essential in the hypoxic-driven milieu of chronic venous leg ulcers (Allen et al, 2013;Fromm-Dornieden and Koenen, 2013;Kim et al, 2007;Nambu et al, 2009;Nie et al, 2011;Park et al, 2008;Sadat et al, 2007). However, AMSC within HDL can assume a pro-inflammatory phenotype, secreting IL-6 and IL-8, when exposed to factors commonly present in a chronic wound, such as Staphylococcus aureus and wound-derived EPI (Sivamani et al, 2014). Timolol, a beta-adrenergic receptor blocker, has been used for decades as a systemic blood pressure lowering agent (Cheng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sivamani et al [26] have shown that the catecholamines released in the wound site decrease the keratinocyte migration mediated by ARs. It has also been described that the activation of β 2 -ARs leads to the in vitro and in vivo inhibition of keratinocytes migration [31, 32], and promotes the recruitment of polymorphonuclear cells by delaying the wound-healing process mediated by the increased IL-6 levels [33]. Furthermore, Shome et al [34] suggested that the neurotransmitter dopamine inhibits the VEGF-induced migration of murine mesenchymal progenitor cells to the wound site in vitro.…”
Section: Discussionmentioning
confidence: 99%